Review and comparison of Mobile Agent Itinerary Planning Algorithms in WSN - Chaudhary, Shivani; Kumar, Umesh; Gambhir, Mohit (International Journal of Computer Sciences and Engineering, 2019)
Wireless sensor networks used the idea of mobile agent to reduce load on network and less energy consumption in comparison to client server based models and obtain effective data gathering. To alleviate the problem of significantly increased latency, data crowding and increased energy consumption in wireless sensor networks, mobile agents (MA) have been proved as the credible substitute to the basic client- server data gathering model. Particularly, in data gathering based on mobile agents, it is very essential to discover the optimal itinerary for the mobile agent dispatched by the sink. In this paper, the existing Mobile Agent based algorithms have been reviewed to address the issues related to data gathering. More significantly, the review showed the advantages and disadvantages of different algorithms and eventually it has also been noted that most of the planning approaches has not considered the security of the collected data by the mobile agent and authentication of the sensor nodes.